Performance and Modelling of PTFE and PTFE plus PANI-based Electrode Modifications in Cylindrical H-Type Microbial Fuel Cells - Akcay, Gizem Hazan; Balbasi, Muzaffer; Ar, Irfan (Taylor & Francis Inc, 2025)
Microbial fuel cells (MFCs) are advanced bioelectrochemical systems that simultaneously treat wastewater and generate electricity using electroactive bacteria as biocatalysts. In this study, different anode and cathode electrodes were modified using PTFE-based and PTFE+Polyaniline (PANI)-based binders combined with activated carbon and expandable graphite, and their effects on MFC performance were evaluated. The maximum power density values were measured at 85,07 mW/m2 for the PTFE-based electrode and 91,86 mW/m2 for the PTFE+PANI-based electrode. The chemical oxygen demand (COD) removal efficiencies were 80,52% and 80,17% and coulombic efficiencies 2,07% and 2% for the PTFE-based and PTFE+PANI-based electrodes, respectively. Additionally, full factorial design optimization was conducted using design expert 7.0.0, and the modeling results were successfully validated. Based on the findings, it can be concluded that the PTFE-based electrode enhances power generation in cylindrical H-type MFCs by improving electron transfer and biofilm formation.
Keywords: Electrode materials; graphite electrode; microbial fuel cell; PANI; PTFE